Portrait of MSME Tourism Financial Management in Sekotong District - Jefri Anwar; Baiq Anggun Hilendri Lestari; Rini Ridhawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Efforts to manage finances for business actors are significant, including tourism MSMEs in Sekotong District. The purpose of this study is to find out how the practice of financial management has been carried out by tourism MSME actors in Sekotong District. This study uses descriptive qualitative research through interviews. Several other sources, such as books and journals, support this study's data. Semi-structured and open-ended interview questions were used as a guide for face-to-face interviews and were recorded with a voice recorder. This study found that only one (1) MSME actor, the lodging business, carried out structured financial management. Meanwhile, the other two (2) MSME actors, namely the Travel Agent and Restaurant businesses, needed to conduct financial management in a structured manner. It is motivated by several factors, namely the lack of knowledge of MSME actors in bookkeeping and the perceived benefits of implementing a bookkeeping system in their respective businesses.